Gluten‐Free Breads: The Gap Between Research and Commercial Reality. Issue 3 (28th March 2019) - Roman, Laura; Belorio, Mayara; Gomez, Manuel
Abstract: The market for gluten‐free products is steadily growing and gluten‐free bread (GFB) keeps on being one of the most challenging products to develop. Although numerous research studies have worked on improving the manufacture of GFBs, some have adopted approaches far from commercial reality. This review analyzes the ingredient list and nutrition facts of 228 commercially available GFBs produced by different brands around the world. The results from studying the ingredient list of breads revealed that commercial breads do not tend to use a single starchy source or gluten replacer, but a combination of several ingredients to optimize bread quality. Maize, tuber starches, and rice flour were the main starchy sources. Regarding hydrocolloids, the most often included ingredients were hydroxypropyl methylcellulose, xanthan and guar gum, and psyllium. Proteins and sugars were added, respectively, in 81% and 87% of the commercial breads analyzed. Furthermore, it was found that vegetable oils were preferred over fats. A long list of ingredients was observed in commercial GFBs, with the presence of a wide range of additives, including acidifiers, emulsifiers, leavening agents, preservatives, and aromas or flavorings. Meanwhile, nutrition facts showed a lower protein and higher fat content for GFBs compared to a gluten‐containing counterpart, with small differences for salt and sugar. This research expands the current knowledge on GFB manufacturing, giving a panoramic outlook on the current situation in the GFB market, and helping both scientists and gluten‐free companies unify/identify common trends.